2014
DOI: 10.1088/0004-637x/798/1/34
|View full text |Cite
|
Sign up to set email alerts
|

The Stickiness of Micrometer-Sized Water-Ice Particles

Abstract: Water ice is one of the most abundant materials in dense molecular clouds and in the outer reaches of protoplanetary disks. In contrast to other materials (e.g., silicates), water ice is assumed to be stickier due to its higher specific surface energy, leading to faster or more efficient growth in mutual collisions. However, experiments investigating the stickiness of water ice have been scarce, particularly in the astrophysically relevant micrometer-sized region and at low temperatures. In this work, we prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
273
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(297 citation statements)
references
References 43 publications
18
273
2
1
Order By: Relevance
“…The accretion rate of these fluffy aggregates onto inner embryos could be greatly different from that of compact aggregates. Bounding and fragmentation of aggregates are also potentially important, but might not be crucial given the sticky nature of ice aggregates (see Wada et al 2009Wada et al , 2011Wada et al , 2013Gundlach & Blum 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The accretion rate of these fluffy aggregates onto inner embryos could be greatly different from that of compact aggregates. Bounding and fragmentation of aggregates are also potentially important, but might not be crucial given the sticky nature of ice aggregates (see Wada et al 2009Wada et al , 2011Wada et al , 2013Gundlach & Blum 2015).…”
Section: Discussionmentioning
confidence: 99%
“…where ρ peb is the density of the pebble itself (set to 1.5 g/cm 3 for water ice) and v f is the fragmentation velocity limit, where waterice particles have a higher fragmentation velocity of 10 m/s than silicate grains (Gundlach & Blum 2015). When we use only this fragmentation limit for icy particles, the Stokes numbers of the particles in our disc model are 0.01-0.2, which is slightly smaller than in the drift-limited case (shown in Fig.…”
Section: Stokes Numbers In the Planet Formation Modelmentioning
confidence: 99%
“…In addition to studies of silica particles, the collisional behavior of water-ice particles was the subject of experimental study. These experiments showed that water-ice particles have an enlarged sticking regime, which is caused by the high surface energy of water (Gundlach & Blum 2015).…”
Section: Introductionmentioning
confidence: 97%